A New Paradigm for Plant Nutrition - Dobermann, Achim; Bruulsema, Tom; Cakmak, Ismail; Gerard, Bruno G.; Majumdar, Kaushik; McLaughlin, Michael; Reidsma, Pytrik; Vanlauwe, Bernard; Wollenberg, Eva Karoline; Fusuo Zhang; Xin Zhang (Springer, 2023)
Nutrient inputs play a critical role in raising crops and livestock for food security, human nutrition and other uses in the bioeconomy. Their production and management must change so as to nourish crops, reduce harmful environmental impacts caused by nutrient losses and contribute to the restoration of soil health more effectively. A new paradigm for plant nutrition follows a food system approach in which multiple socioeconomic, environmental and health objectives must be achieved. The coming 10–20 years will be most critical for making the transition to a global food system in which all stakeholders look at food and nutrients in a holistic manner, including in regard to their hidden environmental, health and socioeconomic costs. Consumers, as well as governments and other stakeholders, need to support such a transformation, because farmers and the industry supporting them will not be able to implement all of the required actions alone. The outcome of this transformation will be a new societal plant nutrition optimum, rather than a purely economic optimum. The new nutrient economy will become an integral component of a low-carbon emission, environment-friendly and circular economy, supporting the food and nutrition requirements of a rising global population and improving the income and livelihood of farmers worldwide.